Large deletions and point mutations involving the dedicator of cytokinesis 8 (DOCK8) in the autosomal-recessive form of hyper-IgE syndrome - AYDINER, ELİF (MOSBY-ELSEVIER, 2009)
Background: The genetic etiologies of the hyper-IgE syndromes are diverse. Approximately 60% to 70% of patients with hyper-IgE syndrome have dominant mutations in STAT3, and a single patient was reported to have a homozygous TYK2 mutation. In the remaining patients with hyper-IgE syndrome, the genetic etiology has not yet been identified. Objectives: We aimed to identify a gene that is mutated or deleted in autosomal recessive hyper-IgE syndrome. Methods: We performed genome-wide single nucleotide polymorphism analysis for 9 patients with autosomal-recessive hyper-IgE syndrome to locate copy number variations and homozygous haplotypes. Homozygosity mapping was performed with 12 patients from 7 additional families. The candidate gene was analyzed by genomic and cDNA sequencing to identify causative alleles in a total of 27 patients with autosomal-recessive hyper-IgE syndrome. Results: Subtelomeric biallelic microdeletions were identified in 5 patients at the terminus of chromosome 9p. In all 5 patients, the deleted interval involved dedicator of cytokinesis 8 (DOCK8), encoding a protein implicated in the regulation of the actin cytoskeleton. Sequencing of patients without large deletions revealed 16 patients from 9 unrelated families with distinct homozygous mutations in DOCK8 causing premature termination, frameshift, splice site disruption, and single exon deletions and microdeletions. DOCK8 deficiency was associated with impaired activation of CD4(+) and CD8(+)T cells. Conclusion: Autosomal-recessive mutations in DOCK8 are responsible for many, although not all, cases of wautosomal-recessive hyper-IgE syndrome. DOCK8 disruption is associated with a phenotype of severe cellular immunodeficiency characterized by susceptibility to viral infections, atopic eczema, defective T-cell activation and T(H)17 cell differentiation, and impaired eosinophil homeostasis and dysregulation of IgE. (J Allergy Clin Immunol 2009;124:1289-302.)
Keywords: Autosomal recessive hyper-IgE syndrome; human gene mutation; DOCK8; primary immunodeficiency; molluscum contagiosum; recurrent infection; T cells; T(H)17 cells; eosinophils; IgE regulation; copy number variations; genomic deletions; IDENTIFICATION; REARRANGEMENTS; GENOME